Experimental Implementation of the Secondary 3 Program of Project P.A.T.H.S.: Observations Based on the Co-Walker Scheme - Daniel T. L. Shek (The Scientific World Journal, 2009)
Classroom observations based on the Co-Walker Scheme were conducted in 34 schools in order to examine the implementation quality of the Tier 1 Program (Secondary 3 Program) of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes) in the Experimental Implementation Phase. Results showed that the overall level of program adherence was generally high (with an average of 82.8%) and the mean ratings of the 13 items examining the implementation quality were all on the high side. Student participation and involvement, and the degree of achievement of the objectives, were the two significant predictors of both overall implementation quality and success of implementation, whereas lesson preparation was the third significant predictor of overall implementation quality. In conjunction with other process evaluation findings, the present study supports that the implementation quality of the Project P.A.T.H.S. is good.